Inverting Thermal Degradation (iTD) of Paper Using Chemi- and Physi-Sorbed Modifiers for Templated Material Synthesis - Gregory, Paul R.; Martin, Andrew; Chang, Boyce S.; Oyola-Reynoso, Stephanie; Bloch, Jean-Francis; Thuo, Martin M. (Frontiers in Chemistry, 2018)
Fibrous cellulosic materials have been used as templates for material synthesis or organization via thermal degradation of the cellulose. Most of these methods, however, fail to exploit fiber organization, in part due to loss of structure with processing. Herein, we demonstrate that chemi- and physi-sorbed modifiers of cellulose alters the thermal degradation mechanism allowing for controlled deposition of oxide and carbon (incomplete combustion) along the original paper fiber network. We demonstrate that the degradation of the cellulose fibers depends on the amount of physisorbed material due, in part, to effect on the propagation of the ignition event. From the distribution of the residual elements and shape of the deposits, we can infer that the thermal degradation process depends on the nature, and concentration, of filler(s) or occluded.